Modified iron oxide nanoparticles as burn rate enhancer in composite solid propellants. (October 2018) - Budhwar, A.S.; Gautam, Aashish; More, Priyesh V.; Pant, Chandra Shekhar; Banerjee, Shaibal; Khanna, Pawan K.
Abstract: The composite solid propellants (CSPs) are the main chemical propulsive force behind missiles and rockets. These propellants consist of pre-polymer (binder), aluminium as fuel and oxidizer with Ammonium perchlorate (AP) as a major oxidant. The burn rate modifier (BRM) is elementary requirement of the AP based composite solid propellants to achieve higher burning rates. The metal oxide nanoparticles are known to act as catalyst in the propellant composition and are the key to enhance the burn rate. Herein, the iron oxide nanoparticles (γ-Fe2 O3 ) were synthesized without and with capping agent (coconut oil) before thoroughly characterized for their phase purity. The results clearly show significant change in burn rate for modified γ-Fe2 O3 nanoparticles when compared to the standard bulk material for similar propellant composition. Graphical abstract: Modified iron oxide nanoparticles were synthesized via a simple co-precipitation method for their application as a burn rate modifier in composite solid propellant. Highlights: In this article, bare and coconut oil capped Fe2 O3 nanoparticles (NPs) were studied for burn rate modifying property. The burn rate modifying property of bare and coconut oil capped Fe2 O3 (NPs) were compared to standard bulk Fe2 O3 particles. The as-prepared Fe2 O3 NPs were characterized and used in fixed proportions (0.5 wt.%) for the composite solid propellants. The studies were performed theoretically and experimentally at desired pressure conditions. The better burn rates were achieved with employment of coconut oil capped Fe2 O3 NPs with certain limitations.